(untitled) (Revista Peruana de Investigación Educativa, 2009)
Mertens, D. (2005). Research and Evaluation in Education and Psychology. Integrating Diversity with Quantitative, Qualitative, and Mixed Methods. 2da. ed. Thousand Oaks, CA: SAGE.